2017
DOI: 10.1111/ecog.02604
|View full text |Cite
|
Sign up to set email alerts
|

Opposed latitudinal patterns of network‐derived and dietary specialization in avian plant–frugivore interaction systems

Abstract: Latitudinal patterns of biodiversity have been studied for centuries, but it is only during the last decades that species interaction networks have been used to examine the proposed latitudinal gradient of biotic specialization. These studies have given idiosyncratic results, which may either be because of genuine biological differences between systems, different concepts and scales used to quantify biotic specialization or because the methodological approaches used to compare interaction networks were inappro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 52 publications
(140 reference statements)
8
145
2
1
Order By: Relevance
“…Dalsgaard and colleagues (Dalsgaard et al 2017) analysed the latitudinal gradient in biotic specialization of avian plant-frugivore networks from two different perspectives, namely niche partitioning in the network and consumers’ dietary specialization, and found opposite results. They showed that network-derived specialization increases with latitude while bird species were more specialized on specific fruit diet in the Tropics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dalsgaard and colleagues (Dalsgaard et al 2017) analysed the latitudinal gradient in biotic specialization of avian plant-frugivore networks from two different perspectives, namely niche partitioning in the network and consumers’ dietary specialization, and found opposite results. They showed that network-derived specialization increases with latitude while bird species were more specialized on specific fruit diet in the Tropics.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors showed an increase in network specialization and higher predation risk towards the tropics (Olesen and Jordano 2002, Dalsgaard et al 2011, Trøjelsgaard and Olesen 2013, Roslin et al 2017), others found the opposite (Schleuning et al 2012). Yet some others found distinct trends for each hemisphere (Pauw and Stanway 2015) and for each measure of biotic specialization considered (Dalsgaard et al 2017), or no latitudinal trend at all (Ollerton and Cranmer 2002, Morris et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated richness of pairwise interactions (links) using the Chao 1 estimator of asymptotic richness (Chao ) with links as “species” and interaction frequencies as “abundances” (Dalsgaard et al. ). Estimated sampling completeness of each network (i.e., observed richness of links divided by the estimated link richness; Dalsgaard et al.…”
Section: Methodsmentioning
confidence: 99%